KAJIAN PENGEMBANGAN MODEL BALANCE SCORECARD UNTUK MENGUKUR DIMENSI KINERJA USAHA MIKRO-KECIL PADAPENGUSAHA MUSLIM DI SULAWESI TENGGARA - La Ode Alimusa; Abdul Rahman; Sitti Zakiah Ma'mum (UMSurabaya Publishing, 2017)
ABSTRACT The purpose of this study is to determine the determinants of dimensions (factor) business performance of Muslim entrepreneurs in Southeast Sulawesi in running a sustainable and competitive advantages. The specific objective is to find a model of alternative business performance measurement of Muslim entrepreneurs which is the development model of Balance Scorecard implementation (BSC) by incorporating the factors of shariah (worship and lawful approach). The method used in this research is Exploratory Factor analysis and qualitative analysis. Sampling method is non-probability sampling with sample size of 10 x 12 variables = 120 sample members (Roscue approach in Sugiyono: 2012). Methods of data collection using in-depth interviews and questionnaires as well as secondary data. Based on the the results of research and discussion it can be concluded that there are 3 main factors that form the dimensions of micro-small business performance is integrated business strategy factors, Internal Business Targets & External Encouragement and Islamic Business Practice Factor. these three dimensions can shape the performance of small micro-enterprises in Muslim entrepreneurs in Southeast Sulawesi about 65%. Thus the integration of the business orientation with the material approach to business practices based on muamalah principles in Islam (Halal orientation and worship) can improve the performance of competitive and sustainable SMEs.Keywords : Business Performance Dimension, development of BSC model, Muslim EntrepreneursCorrespondence to : lalimusa@gmail.com, rahmanfisip@gmail.com, stzakiah132@gmail.com